Impact of movement control order on small - medium enterprise - Ramays, Tharshini R. (2022)
The purpose of this action research is to study the impact of movement control order on small-medium enterprise, a restaurant named Terathai that is located in the Kota masai area. This action research has given an opportunity to increase the reach of the restaurant through digital marketing intervention and increased sales via online delivery. This Restaurant was facing decreased sales due to movement control orders and restrictions imposed by the government. The phenomenon has been investigated in understanding the gap in the current marketing strategy and business development. Based on previous and contemporary studies, digital marketing interventions have been proposed as the solution to improve the sales during pandemic situations. Movement control order has been imposed throughout the country and social distance implemented in the restaurants makes the situation even worse. Thus, this action research enabled the restaurant to explore social media and digital platforms. This action research is based on the goal-oriented Digital Content Marketing (DCM) Model. The Restaurant has subscribed to online food delivery platforms and increased its reach to the people in Kota Masai residential area. Besides, customer engaging content in the forms of social media posts and online brochures have been produced and transmitted via social media and social communication platforms. Upon executing the digital marketing intervention, the impact of the interventions on the sales generated for and the reach of the restaurant across Malaysia have been evaluated. In line with the pragmatism research method, both qualitative and quantitative approaches have been used in answering the research objectives. The reflection gained from this action research is that the digital marketing intervention has impacted positively in generating more sales and improving the visibility of the association across Malaysia. Therefore, future researchers are recommended to further venture into digital marketing intervention towards similar studies.